Reliability and Validity Study of the Turkish Version of Hypomania Checklist-32-Revised - (:unkn) unknown (TURKIYE SINIR VE RUH SAGLIGI DERNEGI, 2016)
Objective: In this study, it is aimed to evaluate the reliability and validity of the Turkish version of Hypomania Checklist-32-Revised. Method: The study was carried out with 80 patients diagnosed with bipolar I disorder, 26 patients diagnosed with bipolar II disorder and 42 patients diagnosed with major depressive disorder attending the out- and in-patient psychiatry departments of three university hospitals and one training hospital, and 116 healthy volunteers consisting of university students. Mean duration of illness was 15,1 years for the bipolar disorder group, and 9,3 years for the major depressive disorder group. For concurrent validity, Mood Disorder Questionnaire was used. In the statistical analysis, internal consistency coefficient, item-total score correlation coefficients, exploratory factor analysis, correlation with concurrent scale and ROC curve were calculated. Results: Translation into Turkish and back-translation into English of Hypomania Checklist-32-Revised were performed and thus the semantic harmony of the scale was obtained. In the internal consistency, Cronbach alpha coefficient was 0,914 and item-total score correlations were between 0,235-0.743. Solely the coefficient of item #23 was found as 0,110. In factor analysis, six factors were obtained but a two-factor solution representing 44,5% of the total variance was accepted and first factor represents overactivity and being expansive, second factor represents impulsivity and risky behaviors. Correlation of Hypomania Checklist-32-R with Mood Disorder Questionnaire was r=0,379. In the ROC analysis, the cut off point of the scale was calculated as 14 with a sensitivity of 71,0 and specificity of 69,8. The scale discriminates well between the bipolar group, and depressive and control groups. Conclusion: Hypomania Checklist-32-Revised developed for screening hypomania is reported to be reliable and valid in Turkish after cutting out item #23.
Keywords: hypomania; checklist; reliability; validity; MOOD DISORDER QUESTIONNAIRE; BIPOLAR SPECTRUM DISORDER; CHECKLIST HCL-32; VALIDATION; SYMPTOMS; INSTRUMENT; THOUGHTS; CRITERIA; SCREEN; MDQ